Face recognition based home security system - Sakib, Sadman; Wadud, M. M. Abdul; Arnob, Fakid Tazbid (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2019.